2005
DOI: 10.1093/jnci/dji250
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Letrozole Following Tamoxifen as Extended Adjuvant Therapy in Receptor-Positive Breast Cancer: Updated Findings from NCIC CTG MA.17

Abstract: Letrozole after tamoxifen is well-tolerated and improves both disease-free and distant disease-free survival but not overall survival, except in node-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
680
0
29

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,042 publications
(722 citation statements)
references
References 41 publications
(14 reference statements)
13
680
0
29
Order By: Relevance
“…[25][26][27][28][41][42][43][44][45][46] Several large studies (Arimidex, Tamoxifen 26,[47][48][49][50] and such therapy has been recommended as part of the standard of care in this patient group. 49,51 Neoadjuvant endocrine therapy also has a role in the treatment of breast cancer, particularly in postmenopausal women with hormone-responsive disease who are unable to tolerate toxicities associated with chemotherapy or who may be ineligible for immediate surgery. 1,17 In these patients, neoadjuvant therapy offers the promise of improving survival or enabling subsequent breast-conserving surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][41][42][43][44][45][46] Several large studies (Arimidex, Tamoxifen 26,[47][48][49][50] and such therapy has been recommended as part of the standard of care in this patient group. 49,51 Neoadjuvant endocrine therapy also has a role in the treatment of breast cancer, particularly in postmenopausal women with hormone-responsive disease who are unable to tolerate toxicities associated with chemotherapy or who may be ineligible for immediate surgery. 1,17 In these patients, neoadjuvant therapy offers the promise of improving survival or enabling subsequent breast-conserving surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen, a selective estrogen receptor modulator, was the standard of care for such patients for nearly 20 years; it can significantly reduce recurrence and breast cancer-related death in patients prescribed about 5 years of adjuvant treatment [1]. However, the third-generation aromatase inhibitors (AIs) anastrozole, letrozole, and exemestane have proven more effective than tamoxifen at improving disease-free survival (DFS), whether given as upfront (initial) adjuvant therapy, as sequential or switch therapy following approximately 2-3 years of prior tamoxifen, or as extended adjuvant therapy following 5 years of tamoxifen treatment [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need for alternative treatments. Treatment with aromatase inhibitors is now proving to be an effective strategy for sequential therapy after 5 years of tamoxifen [21][22][23][24]. More significantly, ATAC and BIG trials have demonstrated superior efficacy of aromatase inhibitors compared to tamoxifen [13,21,25,26].…”
Section: Discussionmentioning
confidence: 99%